TRANSFORMATIONAL LEADERSHIP STYLE DAN WORK ENGAGEMENT KARYAWAN CV L DI UNGARAN - Sadewa Pranata Jati; Sutarto Wijono (Journal of Innovation Research and Knowledge, 2025)
Amid the intense competition today, companies continue to strive to improve efficiency and effectiveness in order to adapt to the ever-evolving competitive dynamics. One effort undertaken is to establish leadership that can inspire and empower employees in facing work-related challenges. Transformational leadership style has become an important factor in fostering work engagement to achieve optimal performance. This study aims to examine the relationship between transformational leadership style and work engagement among employees at CV. L. The method used is quantitative with a correlational design. Data collection employed non-probability sampling with accidental sampling techniques, using a Google Form distributed to 500 employees in the production department at CV. L. The number of participants in this study was 83, determined using the Slovin formula. The research scales used were the Multifactor Leadership Questionnaire (α = 0.903) and the Utrecht Work Engagement Scale (α = 0.976). The Spearman Rho correlation test yielded a coefficient of 0.588 with a significance level (p < 0.05), indicating a positive and significant relationship between transformational leadership and work engagement